The Influence of Abnormal Audit Fee and Auditor Switching Toward Opinion Shopping - Ririn Nawalin; Indah Anis Syukurillah (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
This study examines the influence of abnormal audit fee and auditor switching toward opinion shopping in non-financial company listed in Indonesian Stock Exchange in 2011-2015. The data were analysed using ordinal logistic regression. The results showed that the abnormal audit fee positively influenced opinion shopping, as compared to auditor switching which did not have any effect. Furthermore, company size, ROA changes, leverage changes, company growth; loss and public accounting firm’s (PAF) size were employed as control variables in this study. However, only company size, company growth, loss and public accounting firm’s (PAF) size had effects on opinion shopping. In summary, it is empirically proved that abnormal audit fee affects opinion shopping.